Comparison of anaesthetic cost in open and laparoscopic appendectomy - Demirel, I.; Ozer, A. B.; Kilinc, M.; Bayar, M. K.; Erhan, O. L. (Wolters Kluwer Medknow Publications, 2014)
Context: Appendectomy is generally conducted as open or by laparoscopic surgical techniques under general anesthesia. Aims: This study aims to compare the anesthetic costs of the patients, who underwent open or laparoscopic appendectomy under general anesthesia. Settings and Design: The design is retrospective and records of 379 patients who underwent open or laparoscopic appendectomy under general anesthesia, falling under the category of I-III risk group according to the American Society of Anesthesiologists (ASA) classification between the years 2011 and 2013, and aged 18-77. Subjects and Methods: Open (Group I) or laparoscopic (Group II) appendectomy operation under general anesthesia were evaluated retrospectively by utilizing hospital automation and anesthesia observation records. This study evaluated the anesthesia time of the patients and total costs (Turkish Lira ?, US dollar $) of anesthetic agents used (induction, maintenance), necessary medical materials (connecting line, endotracheal tube, airway, humidifier, branule, aspiration probe), and intravenously administered fluids were evaluated. Statistical Analysis Used: We used Statistical Package for the Social Sciences software (SPSS version 17.0) for statistical analysis. Results: Of the patients, 237 were males (62.53%) and 142 were females (37.47%). Anesthesia time limits were established as 70.30 30.23 minute in Group I and 74.92 31.83 minute in Group II. Mean anesthesia administration cost per patient was found to be 78.79 30.01? (39.16 14.15$) in Group I and 83.09 26.85? (41.29 13.34$) in Group II (P > 0.05). A correlation was observed between cost and operation times (P = 0.002, r = 0.158). Conclusions: Although a statistical difference was not established in this study in terms of time and costs in appendectomy operations conducted as open and laparoscopically, changes may occur in time in market conditions of drugs, patent rights, legal regulations, and prices. Therefore, we believe that it would be beneficial to update and revise cost analyses from time to time.
Keywords: Cost; cost comparison laparoscopic appendectomy; open appendectomy